(untitled) (Brazilian Journal of Health Research, 2021)
Introduction: Given the increasing number of individuals affected by chronic degenerative diseases at global level, the World Health Organization (WHO) has classified the implementation of palliative care in healthcare services as humanitarian need. The resolution addressing guidelines for the organization of palliative care services within the Brazilian Unified Health System was issued in 2018. Objective: Featuring patients followed-up by Palliative Care Service of a University Hospital in Southeastern Brazil. Methods: Descriptive-exploratory study based on analyzing sociodemographic and clinical variables available in both databases and medical records of patients followed-up by the Palliative Care Commission from 2015 to 2017. Descriptive statistics and Chi-square test were applied. Results: In total, 270 patients, mostly brown elderly men, were followed-up during the investigated period. Neoplastic, neurological and cardiovascular issues were the most prevalent diseases. The 10% score Palliative Performance Scale was prevalent; this variable was dependent on other investigated variables. Despite the increased number of hospital discharges, death was the main outcome observed in the current study. Conclusion: Based on patients’ profile, the care provided by the investigated institution is of the end-of-life type, since it faces delayed request. This information can help developing strategies focusing on the expansion of healthcare service.